Characteristics of models that impact transformation of BIMs to virtual environments to support facility management operations - Zou, Zhengbo; Arruda, Luiz; Ergan, Semiha (Journal of Civil Engineering and Management, 2018)
Building information models (BIMs) have been used by the Architectural/Engineering/Construction (AEC) industry with a focus on storing and exchanging digital information about building components. However, the untapped potential of BIMs in facility operations and the experience of facility operators while they interact with digital building information have not been understood widely. One of the underlying bottlenecks in the use of BIMs in the FM phase is the lack of interactions with components to easily access information of interest, and the lack of ways to navigate in models with full spatial understanding. Virtual environments (VEs), which represent physical spaces digitally in virtual worlds, enable interactions with virtual components to access information with spatial understanding. The underlying challenges in the conversion of BIMs to VE hinder a streamlined process. This paper provides a detailed analysis of building size, geometric complexities of discipline models and level of geometric granularity as factors contributing to inefficient transformation of BIMs to VE. The paper also provides research findings on a set of computational approaches such as polygon reduction and occlusion culling to overcome challenges and improve the data transfer faced in converting BIMs into VEs over a range and size of facility models.